2022
DOI: 10.3390/polym14020235
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Biocompatible Polymers by 3D Printing (FDM) on Titanium Alloy

Abstract: Nowadays, the replacement of a hip joint is a standard surgical procedure. However, researchers have continuingly been trying to upgrade endoprostheses and make them more similar to natural joints. The use of 3D printing could be helpful in such cases, since 3D-printed elements could mimic the natural lubrication mechanism of the meniscus. In this paper, we propose a method to deposit plastics directly on titanium alloy using 3D printing (FDM). This procedure allows one to obtain endoprostheses that are more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…11 These polymeric materials can be 3D printed through PBF, or other 3D printing technologies including vat photopolymerization, or extrusion-based 3D printing such as fused deposition modeling. [19][20][21] Nondegradable polymers used in commercial orthopaedic devices include the poly(aryl ether ketone) family inclusive of poly(ether ether ketone), poly(ether ketone), and poly(ether ketone ketone). There are several FDA-cleared devices for spine and craniofacial applications made from poly(ether ether ketone) and poly(ether ether ketone).…”
Section: D Printing Technologiesmentioning
confidence: 99%
“…11 These polymeric materials can be 3D printed through PBF, or other 3D printing technologies including vat photopolymerization, or extrusion-based 3D printing such as fused deposition modeling. [19][20][21] Nondegradable polymers used in commercial orthopaedic devices include the poly(aryl ether ketone) family inclusive of poly(ether ether ketone), poly(ether ketone), and poly(ether ketone ketone). There are several FDA-cleared devices for spine and craniofacial applications made from poly(ether ether ketone) and poly(ether ether ketone).…”
Section: D Printing Technologiesmentioning
confidence: 99%
“…Zimmerman BK et al have studied that different from meniscus dependent on interstitial fluid lubrication, TMJ disc is more relied on boundary lubrication, which needs more in‐vivo studies 12 . Interestingly, Grygier et al have found that polyamide (PA) can show similar friction coefficient to native meniscus 13 . Therefore, more in‐vitro and in‐vivo studies on their lubrication mechanisms can also direct biomaterials selection to mimic the natural lubrication in the future.…”
Section: Functionmentioning
confidence: 99%
“…12 Interestingly, Grygier et al have found that polyamide (PA) can show similar friction coefficient to native meniscus. 13 Therefore, more in-vitro and in-vivo studies on their lubrication mechanisms can also direct biomaterials selection to mimic the natural lubrication in the future.…”
Section: Functionmentioning
confidence: 99%
“…Few publications concern research on friction and wear of polymer materials used in 3D printing. The results presented there concern primarily basic materials such as PLA (Grygier et al, 2022), ABS (Murashima et al, 2017;Perepelkina et al, 2017) or special materials based on polyamide PA (Igus, n.d.-b) used for sliding elements of machines. The influence of 3D printing technological parameters on the tribological properties of these materials is most often determined (Dawoud et al, 2015;Hong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%